2014
DOI: 10.3329/jbau.v12i1.21410
|View full text |Cite
|
Sign up to set email alerts
|

An overview of quality status of selected commercial brands of juices and jams based on public perception and laboratory analysis

Abstract: The study was done to evaluate the quality status of selected commercial brands of juices and jams based on laboratory analysis and public perception. The entire research work was carried out in two phases to evaluate the quality of juices and jams, available in local market. In phase I, a comprehensive baseline survey was done to know the public perception and this revealed that, according to the notion of most respondents, commercial juice and jam products available in market were adulterated by harmful food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…and the Gulf standards (the recommended Microbiological Standards for any fruit juice sold in the Gulf Region 78 . In another study, several kinds of fruit juices showed pH, acidity, total aerobic plate count, yeast-mold count, heavy metal content within the standards recommended by Gulf standards, though the preservative content was higher 79 . Both local and foreign packed and commercial juices are available in Bangladesh.…”
Section: Study Carried Out In Bangladeshmentioning
confidence: 88%
“…and the Gulf standards (the recommended Microbiological Standards for any fruit juice sold in the Gulf Region 78 . In another study, several kinds of fruit juices showed pH, acidity, total aerobic plate count, yeast-mold count, heavy metal content within the standards recommended by Gulf standards, though the preservative content was higher 79 . Both local and foreign packed and commercial juices are available in Bangladesh.…”
Section: Study Carried Out In Bangladeshmentioning
confidence: 88%